2020
DOI: 10.1186/s12936-020-03383-6
|View full text |Cite
|
Sign up to set email alerts
|

Attrition, physical integrity and insecticidal activity of long-lasting insecticidal nets in sub-Saharan Africa and modelling of their impact on vectorial capacity

Abstract: Background: Long-lasting insecticidal nets (LLINs) are the primary malaria prevention and control intervention in many parts of sub-Saharan Africa. While LLINs are expected to last at least 3 years under normal use conditions, they can lose effectiveness because they fall out of use, are discarded, repurposed, physically damaged, or lose insecticidal activity. The contributions of these different interrelated factors to durability of nets and their protection against malaria have been unclear. Methods: Startin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 30 publications
(45 reference statements)
6
57
0
Order By: Relevance
“…In a retrospective study design survival in serviceable condition of DawaPlus ® 2.0 in three locations in Nigeria varied between 42 and 75% (33 percentage-points) after 3 years corresponding to 3.0 to 4.7 years of median survival [ 21 ]. And in a multi-brand, multi-country analysis of durability data from seven countries involving eight LLIN brands survival varied for the same brand between countries from 56 to 98% or by between 10 and 42 percentage-points after 3 years of follow-up [ 24 , Additional file 2, Table S1]. These variations by location are significant and in a similar order of magnitude as observed in this study.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In a retrospective study design survival in serviceable condition of DawaPlus ® 2.0 in three locations in Nigeria varied between 42 and 75% (33 percentage-points) after 3 years corresponding to 3.0 to 4.7 years of median survival [ 21 ]. And in a multi-brand, multi-country analysis of durability data from seven countries involving eight LLIN brands survival varied for the same brand between countries from 56 to 98% or by between 10 and 42 percentage-points after 3 years of follow-up [ 24 , Additional file 2, Table S1]. These variations by location are significant and in a similar order of magnitude as observed in this study.…”
Section: Discussionsupporting
confidence: 67%
“…The data presented in this study suggests that differences in physical durability of LLIN products was driven by the location and not the LLIN brand. This is confirmed by the analysis of a large pooled data set of seven countries and eight LLIN brands followed between 2 and 4 years by Briët et al [ 24 ], that found that for both survival and physical integrity there was significantly more variability of decline of protection over time by country than by LLIN brand. In country by country analysis of the data included in this study DuraNet© was shown to perform significantly better with respect to physical durability than DawaPlus ® 2.0 in DRC [ 28 ] and PermaNet ® 2.0 somewhat better than Olyset™ Net after adjusting for net care attitudes in Zanzibar [ 27 ] suggesting that in specific environments differences by textile characteristics of LLIN do exist.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In Madagascar [49], 55.6% of NetProtect® ITNs were in good condition after a year when compared to Royal Sentry® (56.8%) and Yorkool® (69.2%), which is lower than in the current study, indicating the importance of considering location when estimating ITN durability as cultural in uences, net care and attitudes as well as the physical environment all impact on the expected life of ITNs. In fact, an analysis of PMI-country surveys found that the variation of overall durability of ITNs was larger between countries than among net types, although the durability of net types does vary within countries [50,51]. A literature and data review by Koenker and Yukich [52] found that product attributes do not affect use, agreeing with this study which shows NetProtect® was used equally to the other products but was only found to be more durable in Tanzania.…”
Section: Discussionsupporting
confidence: 71%
“…The purpose of this study was to explore the usefulness of the recently suggested resistance to damage (RD) score as a tool to predict physical performance of LLIN products in the field [ 27 ] and, thereby, allow selection of products based on value for money as proposed by the WHO procurement guideline [ 11 ] rather than price alone. Using the pooled data set of 4672 campaign nets recruited into prospective cohort studies at 10 sites in four African countries allowed to effectively test the hypothesis that products with a higher RD score do, indeed, offer a longer survival in serviceable condition in the field, because it provided standardized and detailed data on net use environment and net care required to adjust for variations in local use conditions which otherwise could have obscured effects of the RD [ 32 ]. The RD scores of the six LLIN brands represented in the study varied from 29 to 63 reflecting the previous finding that current LLIN products not only offer limited variation in RD scores, but also are far from the aspirational level of 100 that represents optimal resistance to hole formation and propagation under reasonable day-to-day use [ 27 ].…”
Section: Discussionmentioning
confidence: 99%